Do aspartate and asparagine acute supplementation influence the onset of fatigue in intense exercise? - Parisi, A.; Quaranta, F.; Masala, D.; Fagnani, F.; Di Salvo, V.; Casasco, M.; Pigozzi, F. (The Journal of Sports Medicine and Physical Fitness, 2007)
Aim: Oxaloacetic acid represents a fundamental intermediary in the metabolism of energy substrate. Asparagine and aspartate constitute precursor compounds of this substance. Therefore, they could affect tricarbossilic acids cycle. Besides, it was suggested that supplementation with aspartate and asparagine determines a muscular glycogen sparing during strenuous physical exercise, even if the real effectiveness remain controversial. The aim of the present pilot study was to evaluate the hypothesis that a supplementation with oxaloacetate precursors, precisely aspartate and asparagine, could improve sport performance during high intensity endurance exercise. Methods: We recruited 15 male trained athletes, aged from 20 to 30 years (mean age: 24.13±3.87 years), practicing triathlon. We administered them placebo or aspartate (7 g) and asparagine (7 g) mixture, using a double blind technique, before performing an exhaustion stress test on cycloergometer carried out to 90% of each athlete's maximum oxygen consumption, previously determined. Results: We evaluated lactatemia through earlobe punctures at the end of warming up, at the maximum effort and at recovery time (3 min, 5 min, 10 min, 15 min, 30 min). Furthermore, subjects were submitted to three blood samples from brachial artery in order to assess the glycemia (before the exercise, at the end of the exercise, and 30 min after the end of the exercise). Conclusion: The analysis of these parameters and the results of the ergometric tests after amino acids assumption indicate that acute supplementation with aspartate and asparagine do not significantly affect physical performance in athletes practicing high intensity exercises, and that acute administration of aspartate does not cause a sparing of muscle glycogen concentration.